Social Construct of Precariousness among the Refugees in the General Hospice of Geneva - TOGBE, Codjo Timothée (My University, 2017)
The Refugees’ living conditions in Europe is triggering nowadays various scientific perspectives and analyses. This article which follows a sociological perspective analyzes some social determinants which structure the precariousness among Refugees in Geneva. Investigations have been carried out along the line of qualitative research method paradigm. Thus, the life story, the semi-structured interview and direct observation using tools such as the interview guide and observation grid have been used in the process. Following the purposeful systematic sampling technique along with the diversification of research areas, 10 actors were approached. The collected data have been processed through content analysis and data triangulation. The theories used are those of the social gradient, misery induced by position, and resilience. It can be inferred from the findings that the legal status of refugees - the type of residence permit and the status of "People without papers" – significantly contributes to the social construct of their precariousness. All the same, a close examination shows the uncertainties related to any successful professional socialization once back in the country of origin, and the fear of being stigmatized as the symbol of patent failure. Those realities coerce the refugees prefer the misery imposed by their living conditions rather than returning home. By way of conclusion, they think it is useless returning home as long as one has not succeeded.
Keywords: Social Construct of Precariousness; Legal Status; Acceptance of Precariousness; Geneva.